Effect of neutralizing agents in the preparation of succinic acid from oil palm trunk. Issue 1 (October 2021) - Bukhari, N A; Loh, S K; Luthfi, A A I; Abdul, P M; Harun, S; Jahim, J M
Abstract: Neutralization is an important process to control the pH required for enzymatic saccharification of pretreated biomass followed by fermentation for biochemical conversion. In this study, the production of succinic acid as a potential C4 building block was investigated by utilizing lignocellulosic biomass in the form of oil palm trunk (OPT). The effect of different neutralizing agents (NaOH, KOH and NH4 OH) on the enzymatic saccharification of oxalic acid-pretreated OPT and subsequent succinic acid fermentation by Actinobacillus succinogenes ATCC 55618 was investigated. The results showed that all neutralizing agents tested were able to assist in the recovery of fermentable sugars with concentrations ranging from 38.1 to 39.6 g/L. However, during succinic acid fermentation, it was found that the soluble NH4 -oxalate salt formed severely inhibited succinic acid fermentation compared to Na and K, thereby decreasing the succinic acid production from 14.0 g/L (using NaOH) to 1.0 g/L (using NH4 OH). In particular, Na-and K-oxalate did not exhibit apparent inhibition for both the saccharification and fermentation processes. Hence, the choice of neutralizing reagent is essential to prevent inhibition in the preparation of succinic acid from lignocellulosic biomass.